Are we choosing wisely for inflammatory bowel disease care? The IG-IBD choosing wisely campaign. Issue 1 (January 2020) - Lenti, Marco Vincenzo; Armuzzi, Alessandro; Castiglione, Fabiana; Fantini, Massimo Claudio; Fiorino, Gionata; Orlando, Ambrogio; Pugliese, Daniela; Rizzello, Fernando; Vecchi, Maurizio; Di Sabatino, Antonio; ,
Abstract: Background: The "Choosing Wisely" campaigns have the aim of promoting a better clinician-patient relationship. Aims: The Italian Group for the Study of Inflammatory Bowel Disease (IG-IBD) conducted a choosing wisely campaign for IBD. Methods: Ten IG-IBD panellists conducted the campaign through a modified Delphi process. All IG-IBD members were asked to submit five statements starting with "Do not…" addressing any IBD-related procedure or treatment the necessity of which should be questioned. All recommendations were evaluated by the panellists who prioritised each item. The top ten recommendations were prioritised again by IG-IBD members, and the top five recommendations were identified. Results: 110 members (mean age 42 ± 12; 62 males) participated in the campaign. The top five recommendations were as follow: 1. Do not use corticosteroids for maintenance therapy, or without a clear indication; 2. Do not forget venous thromboembolism prophylaxis in hospitalised patients with active disease; 3. Do not treat perianal Crohn's disease with biologics without prior surgical evaluation; 4. Do not discontinue IBD-related medications during pregnancy unless specifically indicated; 5. Do not delay surgery. Conclusion: The IG-IBD promoted a campaign with a bottom-up approach, identifying five recommendations that could be useful for providing a better IBD care, especially among non-IBD experts.